Recovery of spent IPA by using evaporation process - Ayesha, Darawin (2012)
Spent Isopropyl Alcohol (IPA) that not recovered must be managed as schedule waste which is quite costly and give significant impact to the environmental issues.Thus,the main objective of this research is to suggest the reuse approach for spent IPA by using simple evaporation process because the IPA is easily to vaporize.The spent IPA recovery is studied by determine the effect of operating temperature and volume of spent IPA to the evaporation process.Besides,by analyzing the concentration of precious metals in the spent IPA,it will guide further research on precious metal recovery.The spent IPA taken from an electronic company will be recovered by using rotary evaporator that is easily to be handled.In the experiments,increasing in temperature will increased the evaporation rate because more heat is transferred to the spent IPA.Therefore,the reusable IPA vapour can easily released since the kinetic energy of spent IPA molecule is also increasing.In varying the spent IPA volume, 98.3% of the spent IPA can be recovered to reusable IPA where another 1.7 % will be in concentrated residual that consists of discarded solder paste in surface mount technology process.Besides,by using atomic adsorption spectrometer,metal concentration after leaching process is 5.214 ppm of copper and 0.8213 ppm of silver.In conclusion, high percentage of spent IPA can be recovered at the optimum temperature 80 oC,and concentration of metal in the spent IPA can be determined.Thus, it is recommended for the electronic company to optimize the usage of IPA.